Evaluating the use of cytosine arabinoside for treatment for recurrent canine steroid‐responsive meningitis‐arteritis. (1st July 2020) - Günther, Christian; Steffen, Frank; Alder, Daniela S; Beatrice, Laura; Geigy, Caroline; Beckmann, Katrin
Abstract : Background: Relapses in steroid‐responsive meningitis‐arteritis (SRMA) are frequently observed but specific treatment protocols to address this problem are sparsely reported. Standard treatment includes prolonged administration of glucocorticoids as monotherapy or in combination with immunosuppressive drugs. The aim of this study was to assess the safety and efficacy of cytosine arabinoside (CA) in combination with glucocorticoids for treatment of SRMA relapses in 12 dogs on a retrospective basis. Methods: Dogs with recurrent episodes of SRMA and treated with a combination of CA and prednisolone were included. Information about clinical course, treatment response and adverse events was collected from medical records. Ethical approval was not required for this study. Results: Ten dogs (10/12) responded well to the treatment with clinical signs being completely controlled. One dog is in clinical remission, but still under treatment. One dog (8%) showed further relapse. Mean treatment period was 51 weeks. Adverse events of variable severity (grade 1–4/5) were documented in all dogs during treatment according to the veterinary cooperative oncology group grading. Three dogs developed severe adverse events. Laboratory findings showed marked changes up to grade 4. Diarrhoea and anaemia were the most often observed adverse events (6), followed by dermatitis (4), alopecia (3) and pneumonia (3). Including blood chemistry changes (13), 50 adverse events were found in total. Conclusion: Treatment with CA and glucocorticoids resulted in clinical remission in 10/12 dogs, but a high incidence of adverse events occurred requiring additional measures. All adverse events could be managed successfully in all cases.